A Study of Exponential-Exponential and Exponentiated Inverted Weibull Distributions for Motor Insurance Claim - Dankunprasert, Sukanda; Talangtam, Tosaporn (Journal of Applied Statistics and Information Technology, 2018)
In this paper, we study the modeling of claim severity and compare these models. The models are Exponential-Exponential (EE), Exponentiated Inverted Weibull (EIW) and Exponential (EXP) distributions which are appropriat for motor insurance claims. The claims data sets of individual claims and aggregate claims are considered. The maximum likelihood estimation (MLE) is used for parameters estimation and the goodness of fit test (GOF) is Kolmogorov-Smirnov test (K-S test). We conclude that the EE, EIW and EXP are appropriate for models for the data of individual claims, aggregated claims by day and aggregated claims by month, respectively.